2023
DOI: 10.19080/arr.2023.08.555732
|View full text |Cite
|
Sign up to set email alerts
|

Cause-Specific Mortality Patterns among Hospital Deaths in District Mardan, Khyber Pakhtunkhwa, Pakistan

Abstract: Background: All the patterns of mortality and encumbrance of diseases in a residential area can be observed from the patients admitted to a hospital. Mortality is the oldest well-known healthcare indicator and an important instrument for planning and well organizes management purposes in hospitals. This study was carried out to evaluate the cause-specific mortality patterns among hospital deaths in Mardan district, Pakistan Methods: The study was conducted between April 2018 to April 2019 in admitted patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…1 Two deaths related to CCHF during the month of May 2023 depict an alarming situation for a country. 8 The health care system in Pakistan is presently not prepared to handle outbreaks of CCHF. A study has revealed that over 40% of health care professionals possess insufficient knowledge regarding CCHF, 7 further exacerbating the situation.…”
mentioning
confidence: 99%
“…1 Two deaths related to CCHF during the month of May 2023 depict an alarming situation for a country. 8 The health care system in Pakistan is presently not prepared to handle outbreaks of CCHF. A study has revealed that over 40% of health care professionals possess insufficient knowledge regarding CCHF, 7 further exacerbating the situation.…”
mentioning
confidence: 99%